Performance Analysis of Modulation Formats in Dispersive Optical Communication System - Singh, Harmanjot (My University, 2008)
With the increasing growth and demand for capacity in national, regional, and even metropolitan optical networks, high bit rate fiber transmission has recently become an essential part of communications. The high bit rate transmission improves spectral utilization which results in increased overall system capacity and reduces overall cost. The optical communication systems are used as high speed long–haul communication systems. To release the potential of optical communication systems and achieve higher transmission capacity at high bit rate, a lot of research on modulates on formats and dispersed managed systems has been done in recent years. The goal of an optical fiber communication system is to transmit the maximum number of bits per second over the maximum possible distance with the fewest errors. The objective of this thesis is, to analyse the performance of dispersed managed RZ system, different modulation formats and to study the different compensation techniques at high bit rate. The dispersed managed system is a promising way to transmit data in optical communication networks. The performance of 10 Gbps optical communication system with the dispersion managed return-to-zero (RZ) pulse has been reported. The return-to-zero (RZ) pulse is efficient for long-distance, high-bit-rate, wavelength division multiplexed (WDM) transmission dispersion-managed systems. In RZ pulse, the power is transmitted only for fraction of bit period. In this thesis, predictions are made by varying the dispersion parameter of single mode fiber in optical communication system. It has been reported that the performance of the system is improved with increase in the value of dispersion parameter. Using the different types of modulation formats, it is predicted that the novel modulation formats enhance the overall performance of the optical communication systems at high bit rate. The performance of non-return-to-zero (NRZ), carrier suppressed return-to-zero (CSRZ) and doubinary modulation format at 10 Gb/s for the optical communication system is analyzed. The performance evaluation of the modulation format has been analyzed in terms of the bit error rate (BER) against the accumulate dispersion and optical signal to noise ratio. The bit rate taken for all the modulation formats is 10 Gb/s. The dispersion tolerance of the modulation formats has been analyzed. The performance of the NRZ, CSRZ and doubinary is analyzed which shows that CSRZ is better for long optical communication system at 10 Gb/s. iv To enhance the overall performance of the optical communication systems, various types of dispersion compensation techniques are used. By using these techniques, the effect of the dispersion can be reduced to great extent. The compensation techniques are fiber based and devices based. In this thesis, the performance of different dispersion compensation techniques with doubinary modulation format at high bit rates is reported. The compensation techniques proposed are dispersion compensation fiber (DCF), reverse dispersion fiber (RDF), negative dispersion fiber (NDF), fiber bragg grating (FBG) and optical phase conjugation (OPC). The comparison of different dispersion compensation techniques at different bit rate has been done. The bit rate is used upto 40 Gb/s. The comparison of different techniques has been analysed from the eye closure, bit error rate and Q- factor characteristics. It has been analysed that the dispersion compensation techniques using combination of standard single mode fiber (SSMF) with dispersion compensation fiber (DCF) and reverse dispersion fiber (RDF) is best suitable for long haul optical communication systems at high bit rates.
M.E. (ECED)
Keywords: Fiber optical communication; modulation; dispersion; impairments; transmission formats